(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Pregnant women’s knowledge and husband’s support are factors that influence antenatal care regularity. This study aims to analyze the effect of knowledge of pregnant women and husband’s support on antenatal care regularity. This study a cross-sectional design and was conducted on 38 pregnant women as respondents using linear regression statistical tests. The result showed that there was an effect of knowledge of pregnant women and the husband’s support on the regularity of antenatal care. The better the knowledge of pregnant women about their pregnancy and the higher the support of their husbands will have an impact on the regularity of antenatal care. The implication of this research is for midwives who are at the forefront of empowering cadres and providing health education to pregnant women and husbands about the importance of regular antenatal care. Also, midwives need to improve competence through midwifery training efforts.